Singapore smart city, smart state - Calder, Kent E. 1948- (Brookings Institution Press, 2016)
"How Singapore's solutions to common problems can provide examples for other societies. Nearly everyone knows that Singapore has one of the most efficient governments and competitive, advanced economies in the world. But can this unique city-state of some 5.5 million residents also serve as a model for other advanced economies as well as for the emerging world? Respected East Asia expert Kent Calder provides clear answers to this intriguing question in his new, groundbreaking book that looks at how Singapore's government has harnessed information technology, data, and a focus on innovative, adaptive governance to become a model smart city, smart state. Calder describes Singapore as a laboratory for solutions to problems experienced by urban societies around the world. In particular, he shows how Singapore has dealt successfully with education, energy, environmental, housing, and transportation challenges; many of its solutions can be adapted in a wide range of other societies. Calder also explains how Singapore offers lessons for how countries can adapt their economies to the contemporary demands of global commerce. Singapore consistently ranks at the top in world surveys measuring competitiveness, ease of doing business, protection of intellectual property, and absence of corruption. The book offers concrete insights and a lucid appreciation of how Singapore's answers to near-universal problems can have a much broader relevance, even in very different societies"...